IMPLEMENTATION OF THE SILABA METHOD IN IMPROVING STUDENTS' PRELIMINARY READING SKILLS IN INDONESIAN LANGUAGE SUBJECTS AT MI AL-MA'ARIF 02 JOMBANG-JEMBER - Rachmawati, Dwi; Fatmawati, Erna; Mu'alimin (ATTA`DIB, 2025)
The initiation of reading stands out as a fundamental skill for students, serving not only as a foundational ability but also as a tool to comprehend the acquired knowledge during their school learning journey. This activity is specially designed for students entering elementary school, playing a pivotal role in their academic development. The syllabic (silaba) method, designed as a syllable-based approach, dissects words into syllables and subsequently reassembles them into complete words. The primary objective is to assist students who encounter difficulties in reading to better grasp and understand words.The primary objective of this study is to assess the effectiveness of the syllabic method in enhancing the initial reading activities of Class II students at MI AL-Ma’arif 02 jombang-jember. Employing a qualitative descriptive method, this research was conducted at Banjarsari 01 Elementary School, situated in Banjarsari Village, Ciawi District, Bogor Regency. A qualitative approach was employed throughout the study, and an interview guide instrument served as the primary tool for data collection. The study incorporated various data collection techniques, including observation, interviews, and documentation. The data analysis technique employed in this study was an interactive approach, aligning with the model proposed by Milles and Huberman. The findings of this study suggest that the syllabic method is indeed an effective approach for initiating reading activities, significantly aiding Class II students at MI AL-Ma’arif 02 jombang-jember in developing their reading skills. Additionally, the syllabic method is considered beneficial for teachers, providing a straightforward and easily comprehensible instructional medium for facilitating learning activities. The required instructional materials for teachers using the syllabic method are both simple and universally understood by students. Notably, the utilization of the syllabic method in the beginning reading activities for Class II students aligns with the specified criteria for the achievement of students' reading activities